Peran Psikologi Pendidikan dalam Mengembangkan Kreativitas Siswa - Sania Mutia Salsabila; Ellen Prima (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Creativity is one of the essential competencies students must possess to face the challenges of the globalization and digital era. However, conventional educational systems often hinder this potential due to an rigid orientation toward cognitive-academic achievement. This study aims to comprehensively analyze the strategic role of educational psychology in fostering and optimizing students' creative potential within the school environment. The research method employed is qualitative with a literature review approach (library research), utilizing secondary data gathered from relevant scientific journals, articles, and theoretical documents. The results indicate that educational psychology provides a scientific foundation for educators to understand mental processes, holistic developmental needs (cognitive, affective, psychomotor), and students' psychological characteristics. Through this approach, the teacher's role is reconstructed from a conventional instructor into an adaptive learning facilitator. Students' creativity can be optimized through the implementation of psychology-based strategies, such as differentiated learning that respects individual uniqueness, and Project-Based Learning methods that stimulate divergent thinking. Furthermore, successful creativity development requires a strong synergy between a positive classroom climate, emotional support within the family environment, and the provision of platforms through extracurricular activities. This study concludes that a proper understanding of educational psychology is the ultimate key to creating a school ecosystem that cultivates a creative, adaptive, and solution-oriented generation.